Monitoramento de impactos ambientais pós-implantação de estações de tratamento de esgotos sanitários - Fajardo, Poliana Arruda (2019)
Among the projects that must be submitted to Environmental Licensing process with Environmental Impact Assessment - EIA in Brazil are the Wastewater Treatment Plants - WWTPs, due to their potential to generate significant negative environmental impacts. A fundamental step of the EIA is the post-implantation monitoring of the projects, as it reinforces the importance and gives meaning to the existence of its main instrument, the environmental impact study. However, researches in several countries, including Brazil, have identified that the post-project impacts monitoring stage has been neglected and the environmental impact studies have been considered as bureaucratic obstacles, whose importance ends in the granting of the Operation License - OL. From this perspective, the actions of the entrepreneurs regarding environmental impacts monitoring based on environmental impact studies are of great importance, as well as the actions of the environmental agencies, responsible for follow-up this monitoring. Thus, the aim of this research was to study aspects of post-project impacts monitoring of WWTPs in São Paulo state, based on its environmental impact study, the Preliminary Environmental Reports - PERs, as well as the actions of the environmental agency, the São Paulo State Environmental Company-CETESB, to follow up that monitoring. As a methodology, a bibliographic research; technical visits to the WWTPs for knowledge and to register observations of the treatment process, as well as getting photographic material to aid in the collection, interpretation and analysis of data were carried out. Interviews with the WWTPs managers, with a technician of Environmental Impact Assessment Board at the headquarters of CETESB in São Paulo, and with CETESB agencies managers were also made. Among the results obtained, the following were observed: the absence of management and monitoring plans in WWTPs PERs; unfamiliarity with the WWTPs PERs by the managers and the station's staff; the consideration by WWTPs managers that PER is a document of the past whose importance comes down to obtaining OL; the absence of post-project impacts monitoring based on PER; and the submission of data by the WWTPs to CETESB referring only to the wastewater treatment, such as the quality of the treated effluent and the river that receives this effluent body. Other results were: the verification of environmental impacts, that occurred or that may occur, not foreseen in the PERs; the contradiction between the managements of WWTPs and CETESB agencies regarding the requirements related to environmental monitoring and the visits by the agencies to the stations; and the lack of political will to implement improvement and problem solving projects, at least in one of the cases. It is considered that the results obtained in this research can subsidize the use and improvement of management and monitoring plans, the elaboration of future environmental impact studies, as well as to contribute to more effective actions of CETESB and WWTPs regarding the monitoring of environmental impacts in the post-implantation stage of WWTPs.